2010
DOI: 10.1021/la102392x
|View full text |Cite
|
Sign up to set email alerts
|

Cross-Linked Network Development in Compatibilized Alkyd/Acrylic Hybrid Latex Films for the Creation of Hard Coatings

Abstract: The modeling provides a correlation between the crosslinked network formation and the resulting mechanical properties.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 39 publications
(112 reference statements)
1
16
0
Order By: Relevance
“…The steady-state CVs represented broad anodic and cathodic peaks ( Figure 6), which were similar to the results in the literature [50]. The proportional relation between the peak current densities the potential scan rates (the insert of Figure 6) suggested that diffusion limits had no effect on the redox processes and the electroactive materials were stick to the working electrode surface [51].…”
Section: Electrochemistry Of R-pte-paa and Pte-paa Filmssupporting
confidence: 86%
“…The steady-state CVs represented broad anodic and cathodic peaks ( Figure 6), which were similar to the results in the literature [50]. The proportional relation between the peak current densities the potential scan rates (the insert of Figure 6) suggested that diffusion limits had no effect on the redox processes and the electroactive materials were stick to the working electrode surface [51].…”
Section: Electrochemistry Of R-pte-paa and Pte-paa Filmssupporting
confidence: 86%
“…Therefore, it seems reasonable to assume that phase migration occurred after water evaporation to be compatible with the pure acrylic polymer; ii) the low molecular weight alkyd resin is expected to be more mobile than the high molecular weight acrylic containing polymer (both pure and grafted [40]);…”
Section: Resultsmentioning
confidence: 99%
“…In situ grafting of growing free‐radicals to the unsaturated alkyd resin increases the compatibility between the two phases and prevents phase separation . Prevention of phase separation in alkyd–acrylic hybrid particles is of major importance in order to promote further homogeneous repartition of the alkyd polymer within the hybrid film . Thus one of the keys to producing useful film‐forming latex will be to understand the relationship between the morphology of the hybrid particles and the formulation used to make them …”
Section: Introductionmentioning
confidence: 99%